Integrating “Hard” and “Soft” Infrastructural Resilience Assessment for Water Distribution Systems - Alessandro Pagano; Irene Pluchinotta; Raffaele Giordano; Umberto Fratino (Complexity)
Cities are highly dynamic systems, whose resilience is affected by the interconnectedness between “hard” and “soft” infrastructures. “Hard infrastructures” are the functional networks with physical elements providing goods or services. “Soft infrastructures” (culture, governance, and social patterns) encompass the social networks, make the hard infrastructures work, and are vital for understanding the consequences of disasters and the effectiveness of emergency management. Although the dynamic interactions between such infrastructures are highly complex in the case of the occurrence of hazardous events, it is fundamental to analyze them. The reliability of hard infrastructures during emergency management contributes to keep alive the social capital, while the community, its networks, and its own resilience influence the service provided by infrastructural systems. Resilience-thinking frameworks overcome the limits of the traditional engineering-oriented approaches, accounting for complexity of socio-technical-organizational networks, bridging the static and dynamic components of disasters across pre- and postevent contexts. The present work develops an integrated approach to operatively assess resilience for the hard and soft infrastructural systems, aiming at modeling the complexity of their interaction by adopting a graph theory-based approach and social network analysis. The developed approach has been experimentally implemented for assessing the integrated resilience of the hard/soft infrastructures during the L’Aquila 2009 earthquake.